Occupational stress and burnout among young surgeons: a review - Dhivakar S.; Rai, Ankit; Sandhu, Harindra; Das, Asish; Subedi, Ram Prasad; Reddy, Kamireddy Madana Raghava (International Journal of Research in Medical Sciences, 2023)
A surgeon’s lifestyle is a multifaceted commitment that revolves around their workplace, physical, personal, emotional, and communal domains. Surgical training programs are competitive and challenging to match and provide a sense of gratification among medical school trainees. But they also report a much higher level of burnout when compared to their peers from other specialities. Workplace burnout has been a scorching issue since the COVID pandemic broke out in 2019. We did this review to understand the factors leading to workplace burnout, identify any East-West differences, and find possible solutions. We also tried to find the role of COVID-19 in worsening occupational stress among surgeons. We searched the PubMed and SCOPUS databases for studies between January 2000 to January 2022 on burnout, well-being, wellness, and practice improvement among surgeons. The search included studies on COVID-19 that were available either as full-text papers or abstracts. Burnout has affected younger surgeons owing to loss of professional control, inefficient work-life balance, administrative burdens, medico-legal problems, and the competitive nature of the job and tiresome training programs. Burnout is more common in South-Asian countries. Workplace stressors, including long hours and difficult interactions with co-workers, are linked to greater levels of burnout. The COVID-19 pandemic has only made matters worse.